1993
DOI: 10.1093/schbul/19.3.461
|View full text |Cite|
|
Sign up to set email alerts
|

Eye Tracking Dysfunction and Schizophrenia: A Critical Perspective

Abstract: Eye tracking dysfunction (ETD) has been found in large numbers of schizophrenia patients and their first-degree relatives. Because of the many replications of the central findings, ETD has been proposed as a useful way of expanding the schizophrenia phenotype in genetic studies. We critically review the literature on ETD with respect to issues of measurement and the search for quantitative indices of ETD; syndrome and familial specificity of ETD for schizophrenia; statistical, interpretive, and methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
199
3
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(211 citation statements)
references
References 172 publications
(609 reference statements)
8
199
3
1
Order By: Relevance
“…In the visual system, deficits have been shown to include increased visual thresholds (Cadenhead et al, 1997;Schechter et al, 2003), greater sensitivity to backward masking (Braff et al, 1991;Butler et al, 1996;Green and Nuechterlein, 1999a;Schechter et al, 2003), and decreased contrast sensitivity (Butler et al, 2005;Keri et al, 2002;Slaghuis and Curran, 1999), as well as motion perception (Chen et al, 1999;Li, 2002;Schwartz et al, 1999) and eye tracking deficits (Holzman et al, 1974;Levy et al, 1993;Trillenberg et al, 2004). Further, it has been suggested that these impairments may contribute to 'upstream' cognitive and social impairments (Brenner et al, 2002;Bruder et al, 1998;Kee et al, 1998;Ohno et al, 2000;Perry and Braff, 1994;Sergi and Green, 2003) and overall functional outcome of patients (Green et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the visual system, deficits have been shown to include increased visual thresholds (Cadenhead et al, 1997;Schechter et al, 2003), greater sensitivity to backward masking (Braff et al, 1991;Butler et al, 1996;Green and Nuechterlein, 1999a;Schechter et al, 2003), and decreased contrast sensitivity (Butler et al, 2005;Keri et al, 2002;Slaghuis and Curran, 1999), as well as motion perception (Chen et al, 1999;Li, 2002;Schwartz et al, 1999) and eye tracking deficits (Holzman et al, 1974;Levy et al, 1993;Trillenberg et al, 2004). Further, it has been suggested that these impairments may contribute to 'upstream' cognitive and social impairments (Brenner et al, 2002;Bruder et al, 1998;Kee et al, 1998;Ohno et al, 2000;Perry and Braff, 1994;Sergi and Green, 2003) and overall functional outcome of patients (Green et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Visual motion processing has been studied to explore the neurological underpinnings of eyetracking dysfunction in schizophrenia (Holzman et al, 1973(Holzman et al, , 1974Sweeney et al, 1992;Levy et al, 1993;Friedman et al, 1995;Stuve et al, 1997;Chen et al, 1999a,b,c). Motion processing has also been studied in normal aging (Owsley et al, 1983;Ball and Sekuler, 1986;Gilmore et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported impaired smooth pursuit eye movements in bipolar patients (Shagass et al, 1974;Levin et al, 1981;Iacono et al, 1982;Holzman et al, 1984), whereas other studies showed no difference between affective disorder patients and controls (Holzman et al, 1974;Iacono et al, 1992;Friedman et al, 1995). Several studies found that relatives of affective disorder patients and controls did not differ in eye tracking performance (Levy et al, 1983(Levy et al, , 1993Rosenberg et al, 1997; but see Kathmann et al, 2003). Treatment with lithium carbonate has been associated with poor eye tracking in individuals with bipolar disorder (Levy et al, 1985;Holzman et al, 1991) and in relatives who themselves were being treated for bipolar disorder (Levy et al, 1983(Levy et al, , 1985, although one study failed to show this effect (Gooding et al, 1993).…”
mentioning
confidence: 99%